Métodos não judiciais de resolução de conflitos na política judiciária nacional de tratamento adequado das disputas de interesses no âmbito do poder judiciário trabalhista: uma análise comparativa da Comissão de Conciliação Prévia e do Sistema Núcleo Intersindical de Conciliação Trabalhista - Jacqueline Ferreira Torres (2018)
The promulgation of the Constitution of the Federative Republic of Brazil of 1988 - CRFB / 88 - represents the inauguration of a new constitutional order in the country, as well as the assumption of the commitment to build a society based on its principles and assumptions. Inevitably, the search for this social project presupposes changes in traditional structures and the adaptation of the state apparatus to the new institutional paradigm. Despite of the constant adjustments and reforms, the Judiciary remain operating below social demands and expectations, generating dissatisfaction, a phenomenon that was called the crisis of the Judiciary. In order to overcome this crisis, a public policy of Administration of Justice has been established with guidelines for the improvement of judicial and extrajudicial mechanisms of resolution of disputes and for the adequate treatment of conflicts of interest. The present research aims to compare the previous experiences of the Previous Reconciliation Commissions - CCP - and the Inter-Union Nucleo of Labor Conciliation - NINTER - to understand their potential for the development of the judicial policy. In order to achieve this objective, the an extensive diagnosis of the Brazilian Judiciary in the paradigm of the Democratic State of Law was made, seeking to understand the necessary changes in its role for the realization of social rights. Then, we analyzed how the paradigmatic change took place in the Administration of Justice in the country. Based on this analysis, and on the understanding of the incentive of extrajudicial methods of conflict resolution as a State policy, we compared the institutes of the CCP and the NINTER. Considering their structures and their results, it was possible to establish a wide differentiation between the institutes, concluding that the Inter-Union Nucleo of Labor Conciliation - NINTER effectively contribute to the development of the national policy for the adequate treatment of conflicts of interest within the scope of the Labor Judiciary.